2006
DOI: 10.1016/j.febslet.2006.09.063
|View full text |Cite
|
Sign up to set email alerts
|

αB‐crystallin competes with Alzheimer's disease β‐amyloid peptide for peptide–peptide interactions and induces oxidation of Abeta‐Met35

Abstract: Alzheimer's disease (AD) is associated with plaque deposition in the brain of AD patients. The major component of the aggregate is a 39-42 long peptide termed b-amyloid (Ab). Except for Ab, plaques contain several other components which co-precipitate together with Ab. One such component is the small heat shock protein (sHSP) aB-crystallin. Instead of preventing the cell from the neurotoxicity of Ab, aB-crystallin induces an increased neurotoxicity.We find -using solution state NMR spectroscopy -that aBcrystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 39 publications
9
51
0
Order By: Relevance
“…KFVIF; the corresponding peptide region in αB-crystallin is RFSVN) has strong sequence similarity to a region of the fibril-forming core domain of Aβ(1-40), KLVFF [102,141]. This region in Aβ(1-40) has recently been shown by NMR spectroscopy to be primarily involved in the interaction between Aβ(1-40) and αB-crystallin [142]. Moreover, KLVFF of Aβ(1-40) facilitates the elongation of fibrils formed from Aβ.…”
Section: The Region(s) Of α-Crystallin Responsible For Target Proteinmentioning
confidence: 99%
“…KFVIF; the corresponding peptide region in αB-crystallin is RFSVN) has strong sequence similarity to a region of the fibril-forming core domain of Aβ(1-40), KLVFF [102,141]. This region in Aβ(1-40) has recently been shown by NMR spectroscopy to be primarily involved in the interaction between Aβ(1-40) and αB-crystallin [142]. Moreover, KLVFF of Aβ(1-40) facilitates the elongation of fibrils formed from Aβ.…”
Section: The Region(s) Of α-Crystallin Responsible For Target Proteinmentioning
confidence: 99%
“…Investigation of the dynamics of the C-terminus of αB-crystallin showed the importance of this region for the solubility of αB-crystallin complexes [300]. Saturation transfer difference (STD) experiments showed that αB-crystallin interacts with the hydrophobic core of A [301]. Furthermore, the ability of αB-crystallin to prevent oligomerization and the oxidation of Met35 was established, whereas the oxidation of Met35 in A induces an increased neurotoxicity, since the oxidized form facilitates the propagation of free radicals among adjacent residues [301][302][303].…”
Section: B-crystallinmentioning
confidence: 99%
“…Saturation transfer difference (STD) experiments showed that αB-crystallin interacts with the hydrophobic core of A [301]. Furthermore, the ability of αB-crystallin to prevent oligomerization and the oxidation of Met35 was established, whereas the oxidation of Met35 in A induces an increased neurotoxicity, since the oxidized form facilitates the propagation of free radicals among adjacent residues [301][302][303]. Based on combined NMR, PRE and relaxation experiments, as well as mass spectroscopy, a comprehensive picture of αB-crystallin emerges in which quaternary dynamics and oligomeric distribution due to monomer exchange on a timescale of minutes are connected to structural fluctuations in the C-terminus on the millisecond timescale [304,305].…”
Section: B-crystallinmentioning
confidence: 99%
“…On the basis of previous work on various other small molecule modulators of A␤ aggregation, such as 8-hydroxyquinolines (42), oleuropein (43,44), ␣-helix stabilizers (45), various chaperones (46,47), anesthetics (48,49), and gangliosides (50), two potential binding sites can be suggested. From these previous studies it is clear that A␤ contains a small molecule binding site near residues 10 -20 and a second binding site in the C-terminal glycine zipper motif.…”
Section: Samplementioning
confidence: 99%